The Distributional Consequences of Increasing Tobacco Taxes on Colombia’s Health and Finances : An Extended Cost-Effectiveness Analysis - James, Erin (World Bank, Washington, DC, 2017)
Since 2008, when Colombia ratified the Framework Convention for Tobacco Control, available evidence of the impact of tobacco consumption, its health effects, and low tax revenues resulting from low tobacco taxation and prices had grown. By 2015, Colombia’s cigarette prices stood higher than only one other country in the region, and smoking had become the second leading modifiable risk factor for premature mortality. At that time, reduced fiscal revenues resulting from a sharp drop in oil prices, accompanied by growing demand for government spending arising partly from a change in legislation that increased health benefits for the lower socioeconomic population, led to a call for tax reform. The preparation of the document was accompanied by technical training, studies, and public fora with national and international experts, civil society, and academia presenting evidences and arguing for increased taxation to lead to a reduction in tobacco consumption and, in the future, a reduction in costs to the health system. The fora and open dialogue helped align strategies of the Ministry of Health and Social Protection, and the Ministry of Finance in presenting the reform to Congress for approval with a larger academic and civil society support for this measure. In December 2016, resulting from the above-mentioned efforts, Colombia passed a major tax increase on tobacco products with the goal of decreasing smoking and improving population health. While tobacco taxes are known to be highly effective in reducing the prevalence of smoking, they are often criticized as being regressive in consumption. This analysis attempts to assess the distributional impact (across income quintiles) of the new tax on selected health and financial outcomes.